Problems of Extension of Primary Education in Rural Areas - Planning Commission (Planning Commission, 1965)
One of the major aims of the Third Five Year Plan is “to expand and intensify the educational effort and to bring every home within its fold, so that from now on, in all branches of national life, education becomes the focal point of planned development”1. In placing this emphasis on educational programmes in the Third Plan, The Planning Commission recognised that there were “large deficiencies in the sphere of education which must be removed speedily if progress is to be sustained and enduring”. Among the programmes in the field of general education that have received special emphasis in the Third Plan.
Programme Evaluation Organisation, Planning Commission, Government of India